2015
DOI: 10.3109/00016357.2015.1044562
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence and enamel defects in 5- and 10-year-old children with cleft lip and/or palate: A case-control study

Abstract: Preschool children with cleft lip and/or palate seem to have more caries in the primary dentition than age-matched non-cleft controls. Enamel defects were more common in CL(P) children in both age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 26 publications
3
30
0
6
Order By: Relevance
“…Clefts, cases in the sample having cleft lip history shows different degrees of enamel hypoplasia and hypocalcification this was assured by certain study (52) that found that there was a significant relationship was found between the cleft side and enamel defects, the highest prevalence on the cleft side suggests that the cleft does influence the occurrence of enamel defects in permanent teeth, this were in agreement with other studies (35,53) and more recently (54) where enamel defects was more common in CL(P) children in both primary and permanent dentition.…”
Section: Concerning Cases Of Previously Repairedsupporting
confidence: 81%
“…Clefts, cases in the sample having cleft lip history shows different degrees of enamel hypoplasia and hypocalcification this was assured by certain study (52) that found that there was a significant relationship was found between the cleft side and enamel defects, the highest prevalence on the cleft side suggests that the cleft does influence the occurrence of enamel defects in permanent teeth, this were in agreement with other studies (35,53) and more recently (54) where enamel defects was more common in CL(P) children in both primary and permanent dentition.…”
Section: Concerning Cases Of Previously Repairedsupporting
confidence: 81%
“…In our population, this was higher (at 54%) and this may represent an underestimate as children with missing teeth could not be scored. Other studies have reported a higher prevalence of DDE in children with clefts . The aetiology of DDE is not entirely clear, but it has been associated with poor maternal health during pregnancy, pre‐term birth and hospitalization in the first year of life; the majority of these children would have been admitted to hospital in their first year of life for cleft repair operations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, untreated and open caries lesions are associated with increased lactobacilli counts [28]. The frequent occurrence of enamel defects (hypoplasia and hypomineralisation) in this CL(P) material [6] can also act as retention sites for plaque and may contribute to the elevated counts of salivary lactobacilli. However, in the Cariogram model, the lactobacilli counts are entered to reflect the “sugar amount” in the diet but, unfortunately, we had no detailed information on the dietary habits in the present study groups.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CL(P) and dental caries in children is not fully clear but a number of studies indicate a higher caries prevalence in children with different oral clefts in comparison with non-cleft controls [2–6]. Several factors can contribute to this higher susceptibility such as impaired oral hygiene [2, 5, 7, 8], enamel hypoplasia [9, 10] and early colonization of caries-associated microorganisms [11].…”
Section: Introductionmentioning
confidence: 99%